2000
DOI: 10.1074/jbc.275.2.890
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the GTPase Activity of Translation Elongation Factor G by Ribosomal Protein L7/12

Abstract: Elongation factors (EFs) Tu and G are GTPases that have important functions in protein synthesis. The low intrinsic GTPase activity of both factors is strongly stimulated on the ribosome by unknown mechanisms. Here we report that isolated ribosomal protein L7/12 strongly stimulates GTP hydrolysis by EF-G, but not by EF-Tu, indicating a major contribution of L7/12 to GTPase activation of EF-G on the ribosome. The effect is due to the acceleration of the catalytic step because the rate of GDP-GTP exchange on EF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 48 publications
(52 reference statements)
5
84
2
Order By: Relevance
“…Using mant-GTP as a fluorescent reporter, we observed that its fluorescence increased substantially when wild type EF-G was added (Fig. 3A), as reported previously (21). When we subsequently added a limiting amount of the ribosome, the fluorescence gradually dropped to a lower plateau.…”
Section: Figure 1 Locations Of Mutated Residues In the G Subdomain Osupporting
confidence: 64%
“…Using mant-GTP as a fluorescent reporter, we observed that its fluorescence increased substantially when wild type EF-G was added (Fig. 3A), as reported previously (21). When we subsequently added a limiting amount of the ribosome, the fluorescence gradually dropped to a lower plateau.…”
Section: Figure 1 Locations Of Mutated Residues In the G Subdomain Osupporting
confidence: 64%
“…The overall similarity in these determinations gives us greater confidence in the reported binding data. Taken together, our data suggest that GTP binding should predominate if nucleotide-free RF3 were simply incubated in the cellular milieu; however, given that RF3:GDP leaves the ribosome and must bind to GTP to function in the next cycle, there remains a kinetic problem (Savelsbergh et al 2000;Gromadski et al 2002). The off-rates of GDP from RF3 are slow enough that a GEF is likely needed to increase the rate of nucleotide exchange to physiologically relevant levels.…”
Section: Discussionmentioning
confidence: 94%
“…While the levels of GTP are eightfold higher than GDP in the cell (1660 μM vs. 233 μM, respectively) (Buckstein et al 2008), it is not clear how GDP for GTP exchange can happen on a physiologically relevant time scale in the cell in the absence of a GEF that promotes more rapid nucleotide exchange. Indeed, the off-rates of nucleotides from two other translational GTPases, EFTu and EFG, differ greatly from one another: in the case of EFG, the off-rates are relatively fast (k off,GDP = 23 sec −1 and k off,GTP = 7 sec −1 ) (Savelsbergh et al 2000), while in the case of EFTu, the off-rates are significantly slower (k off,GDP = 0.002 sec −1 , k off,GTP = 0.03 sec −1 ) (Gromadski et al 2002). It is, thus, not surprising that EFTu has a dedicated GEF in the cell, EFTs, while EFG functions as far as is known without any GEF.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that isolated L7/L12 ribosomal proteins were able to stimulate GTP hydrolysis on EF-G to some extent. 52 However ribosomes lacking the L7/L12 were still able to hydrolyze GTP on EF-G (although at a reduced rate), 10,53 thus arguing for additional ribosomal components involved in GTPase activation. It is likely that the primary role of the L7/L12 stalk is factor recruitment rather than GTPase activation.…”
mentioning
confidence: 99%